Patrones de actividad y diversidad de mamíferos para una propuesta de conservación del bosque seco tropical en Reserva Natural Punta Gorda - Miranda Ibarra, Alfonso Sebastián (2024)
The main objective of this research was to monitor the mammals present in the Tropical Dry Forest, specifically in the Punta Gorda Natural Reserve located 8 km south of the city of Bahía de Caráquez, in order to create a proposal for its conservation. This research was descriptive observational, based on the observation, description and registration of mammals, which were identified and compared activity patterns, as well as their abundance; within the methods used we have the analytical method, bibliographic method, inductive method and field method, as well as monitoring techniques with camera traps, data collection and observation. A total of 10 different mammals were recorded, one of which has a very sensitive conservation status, namely the coastal capuchin monkey (C. aequatorialis), and the most abundant species recorded were the white-tailed deer (O. peruvianus) and the peccary (P. tajacu). This research determined that the index of mammal biodiversity in the Punta Gorda Natural Reserve is low, which is defined as the number of mammals in the reserve as a percentage of the total number of mammals in the reserve.